My Math Forum sin(z) = -1 - i with solutions (need explanation)
 User Name Remember Me? Password

 Complex Analysis Complex Analysis Math Forum

February 5th, 2017, 10:50 AM   #1
Newbie

Joined: Jan 2017

Posts: 21
Thanks: 0

sin(z) = -1 - i with solutions (need explanation)

So I look at the prof's solutions - see attached.

I dont understand how he got from (coshy)^2 + (sinhy)^2 = (sinhy)^2(coshy)^2 to

cosh2y = 1/4(sinh2y)^2

Then
cosh2y = sqrt(5) +2
y = (1/2)ln(sqrt(5)+2 +/- sqrt(8+4sqrt(5))

Then
sinx = 2-sqrt(5)
x= 2pi - sin(sqrt(5)-2)^-1 + 2kpi

Can someone explain?
Attached Images
 Screen Shot 2017-02-05 at 3.47.06 AM.jpg (19.3 KB, 11 views)

 February 5th, 2017, 11:08 AM #2 Senior Member     Joined: Sep 2015 From: USA Posts: 1,981 Thanks: 1027 basic identity $\cosh(a+b)=\cosh(a)\cosh(b) + \sinh(a)\sinh(b)$ let $a=b=y$ $\cosh(2y) = \cosh^2(y) + \sinh^2(y)$ basic identify $\sinh(a+b) = \sinh(a)\cosh(b)+\cosh(a)\sinh(b)$ again let $a=b=y$ $\sinh(2y) = 2\sinh(y)\cosh(y)$ $\dfrac{\sinh(2y)}{2} = \sinh(y)\cosh(y)$ $\dfrac{\sinh^2(2y)}{4} = \sinh^2(y)\cosh^2(y)$ This link has a good explanation of how $\cosh^{-1}(y) = \log(y\pm\sqrt{y^2-1}),~y>1$ Thanks from topsquark
February 5th, 2017, 11:30 AM   #3
Newbie

Joined: Jan 2017

Posts: 21
Thanks: 0

Quote:
 Originally Posted by romsek basic identity $\cosh(a+b)=\cosh(a)\cosh(b) + \sinh(a)\sinh(b)$ let $a=b=y$ $\cosh(2y) = \cosh^2(y) + \sinh^2(y)$ basic identify $\sinh(a+b) = \sinh(a)\cosh(b)+\cosh(a)\sinh(b)$ again let $a=b=y$ $\sinh(2y) = 2\sinh(y)\cosh(y)$ $\dfrac{\sinh(2y)}{2} = \sinh(y)\cosh(y)$ $\dfrac{\sinh^2(2y)}{4} = \sinh^2(y)\cosh^2(y)$ This link has a good explanation of how $\cosh^{-1}(y) = \log(y\pm\sqrt{y^2-1}),~y>1$

Thanks! that helped a lot!

Do you know why he set sinx = 2 - sqrt(5) though?

February 5th, 2017, 11:40 AM   #4
Newbie

Joined: Jan 2017

Posts: 21
Thanks: 0

Quote:
 Originally Posted by romsek basic identity $\cosh(a+b)=\cosh(a)\cosh(b) + \sinh(a)\sinh(b)$ let $a=b=y$ $\cosh(2y) = \cosh^2(y) + \sinh^2(y)$ basic identify $\sinh(a+b) = \sinh(a)\cosh(b)+\cosh(a)\sinh(b)$ again let $a=b=y$ $\sinh(2y) = 2\sinh(y)\cosh(y)$ $\dfrac{\sinh(2y)}{2} = \sinh(y)\cosh(y)$ $\dfrac{\sinh^2(2y)}{4} = \sinh^2(y)\cosh^2(y)$ This link has a good explanation of how $\cosh^{-1}(y) = \log(y\pm\sqrt{y^2-1}),~y>1$

Thanks! that helped a lot!

Do you know why he set sinx = 2 - sqrt(5) though?

 February 5th, 2017, 04:54 PM #5 Member   Joined: Oct 2016 From: Melbourne Posts: 77 Thanks: 35 It's because the solution to the quadratic equation \displaystyle \begin{align*} x^2 - 4\,x - 1 = 0 \end{align*} is \displaystyle \begin{align*} x = \frac{4 \pm \sqrt{20}}{2} = \frac{4 \pm 2\,\sqrt{5}}{2} = 2 \pm \sqrt{5} \end{align*}. Thanks from topsquark

 Tags explanation, sinz, solutions

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post sadmath Geometry 8 September 13th, 2015 06:24 AM rain Calculus 3 July 19th, 2013 11:21 PM daivinhtran Algebra 5 July 24th, 2011 11:54 AM mattman059 Linear Algebra 2 March 6th, 2009 07:24 AM rain Real Analysis 3 December 31st, 1969 04:00 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top